Exploring the Impact of Parenting Styles on Children’s Academic and Mental Health - Qian, Wenxu (Journal of Ecohumanism, 2024)
(Objective) This article examines how different parenting styles relate to children’s academic and psychological adjustment, focusing on scholastic engagement, persistence, emotional resilience, and stress management. (Method) The study reviews empirical research through the lens of Basic Psychological Need Theory and Self-esteem Theory, analyzing four parenting styles: authoritarian, authoritative, permissive, and uninvolved. (Results) The findings emphasize the importance of academic adjustment for scholastic achievement and psychological adjustment for emotional well-being. The study highlights the need for an encouraging family environment, effective parenting methods, and educational interventions to promote children’s academic and psychological development. Further research is required to understand the mechanisms by which parenting styles influence child adjustment.